Outcomes Following Severe Distal Tibial, Ankle, and/or Mid/Hindfoot Trauma: Comparison of Limb Salvage and Transtibial Amputation (OUTLET). (1st September 2021) - Bosse, Michael J.; Carroll, Eben A.; Firoozabadi, Reza; Gary, Joshua L.; Gordon, Wade T.; Jones, Clifford B.; Morshed, Saam; Teague, David; Scharfstein, Daniel O.; Luly, Jason; MacKenzie, Ellen J.; Reider, Lisa; et al.
Abstract : Background: Selecting the best treatment for patients with severe terminal lower-limb injury remains a challenge. For some injuries, amputation may result in better outcomes than limb salvage. This study compared the outcomes of patients who underwent limb salvage with those that would have been achieved had they undergone amputation. Methods: This multicenter prospective observational study included patients 18 to 60 years of age in whom a Type-III pilon or IIIB or C ankle fracture, a Type-III talar or calcaneal fracture, or an open or closed blast/crush foot injury had been treated with limb salvage (n = 488) or amputation (n = 151) and followed for 18 months. The primary outcome was the Short Musculoskeletal Function Assessment (SMFA). Causal effect estimates of the improvement that amputation would have provided if it had been performed instead of limb salvage were calculated for the SMFA score, physical performance, pain, participation in vigorous activities, and return to work. Results: The patients who underwent limb salvage would have had small differences in most outcomes had they undergone amputation. The most notable difference was an improvement in the SMFA mobility score of 7 points (95% confidence interval [CI] = 2.0 to 10.7). Improvements were largest for pilon/ankle fractures and complex injury patterns. Conclusions: Amputation should be considered a treatment option rather than a last resort for the most complex terminal lower-limb injuries. Level of Evidence: Therapeutic Level II . See Instructions for Authors for a complete description of levels of evidence.